Nokia’s Growing Cash Mountain - Rahnema, Ahmad (Senate Hall Academic Publishing, 2005)
As of mid-November 2002, Jorma Ollila, CEO of Nokia must decide a course of action for his company’s growing ‘cash pile’ of eight billion euros. The company does not have any immediate acquisitions on the horizon and boasts a low debt load – €450 million in long-term debt and €2.6 billion in customer financing exposure. Ollila has recently ruled out a share buy-back after credit agencies like Moody’s threatened to downgrade the company from its current A1 credit rating. Ollila needs to come up with a plan for the cash within two weeks that will suit shareholders and Nokia’s future investment needs.
Keywords: dividend policy; cash dividend; share-buy-back; financial policy; cash pile; mobile telecommunication